Perencanaan Pemasaran Tahu Tuna pada Usaha Mikro Nabilla Makmur di Pacitan, Jawa Timur - NI LUH MADE RATNA HAPSARI PUTRI; DWI PUTRA DARMAWAN; PUTU UDAYANI WIJAYANTI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Marketing Plan of Tuna Tofu at Micro Enterprise Nabilla Makmur in Pacitan, Eats Java This study aimed to know the marketing plan of tuna tofu micro business of NabillaMakmur in 2017 as a new pioneered business unit and having a bright salesprospect.. The data analysis used Smart Business Plan 8.0 program consisting ofmarketing plan variables. The company did not implement the target in sales, butwithin one month the company was able to produce up to 1,500 packs per month.Based on the results of internal and external factors analysis by maximizing thestrength and exploiting the existing opportunities and minimizing the weaknessesand threats from outside by improving the quality of tuna tofu products and servicesto consumers, looking for new potential supplier areas, promotion through internetand mass media and additional personnel as company sales, and cooperation with giftshop around Pacitan.The strategy adopted by the company was a marketing mixstrategy which consists of product strategy using packaging system using vacuumplastic, pricing strategy based on competitor price, and cost of principle sale price indetermining selling price of tuna tofu, company distribution strategy through localsales in Pacitan city and sales in out of Pacitan city covering some big cities inIndonesia, company promotion strategy with good company name and through socialmedia.